Editorial for the Special Issue, ‘Secondary Metabolites from Microorganisms or Microorganism–Host Interaction?’ - Fengli Zhang; Michel Denis (Biology, 2023)
In this Special Issue, there are 13 published papers from over 10 countries [...]